Узгодження параметрів зварювальних імпульсів з програмою тиску електродів та електрофізичними процесами в зварювальному контакті - Bondarenko, Oleksandr (PE "Politekhperiodika", Book and Journal Publishers, 2019)
Resistance welding is an important technological operation for many modern industries, including mechanical engineering, electronics and instrument making. Micro resistance welding is used in producing of micro-structures for critical purposes, such as electronic components, circuits, etc. It is obvious that welded joints in such structures should be characterized by such high quality indicators as the absence of solid metal splashes, burnouts, faulty fusions, and the repetitiveness of dimensions of welding spots, which are achieved by coordinating the parameters of welding current pulses with electrophysical processes in welding contact.Thus, in this paper, the authors analyze electrophysical processes taking place in the welding contact and the effect of the welding current pulse parameters on these processes, in order to mutually coordinate them. This allows specifying the law of pulse power change, which makes it possible to take into account the features of electrophysical processes in the welding contact to the full extent. The smooth rise of the pulse power, obtained according to the exponent law with selection of the optimal exponent n value, provides gradual input of energy required for welding during the most unstable phase of primary contact formation.Due to the flat top of the welding pulse, the constant energy input to the contact is maintained during a rather stable phase of welding core formation. Finally, the smooth pulse fall obtained by selecting the optimal exponent m value of the power change law provides the proper cooling of the welding spot, which guarantees the strength and uniformity of the joint structure. To achieve the best welding quality, the recommendations are given regarding the formation of rise and fall of the pulse, depending on specific welding conditions, parameters of the welded parts and requirements for the obtained joints.The paper shows that it is a useful practice to coordinate the pulse power change law with the program of changing the pressure of the electrodes, and with changing the resistance of the welding zone. The proposed example of coordination between welding pulse power change, welding electrode pressure and electrophysical processes in the welding contact (resistance of the welding zone) is substantiated in terms of the influence of the electrode pressure on the welding process. This practice can provide the highest quality of welded joints and thus the highest quality of the end products manufactured by welding.